Synthesis and Characterization of Styrene-Acrylic Binders and Their Application on Pigment Printing of Cotton and Polyester Textile Fabrics - NAJAFI, HOSSEIN; ESMAIL YAZDANSHENAS, MOHAMMAD; RASHIDI, ABOSAID; MONTAZER, MAJID (Asian Journal of Chemistry, 2010)
This paper reports the synthesis and characterization of styreneacrylic binders. 2-Ethylhexylacrylate styrene (2-EHA), ethyl acrylate styrene (EA), methyl methaacrylate styrene (MMA), butyl acrylate styrene (BA) copolymers were prepared by emulsion copolymerization. The polymerization was performed with methaacrylic acid (MAA) and auxiliary agents at 80 ºC in the presence of ammonium persulphate (APS) as the initiator. Sodium lauryl ether sulphate was used as non-ionic emulsifier. The resulting copolymers were characterized by Fourier transform infrared spectroscopy (FTIR) and then effect of initiator on the properties of the styrene-acrylic binders emulsion copolymers were discussed. A printing paste comprising synthetic thickener, emulgator, styrene-acrylic binders, Imperon brilliant red B was applied using a flat screen printing technique on to the cotton and polyester fabrics, then dried and exposed to heat in different temperature. The characteristics of cured prints such as paste add-on, colour fastness to washing and dry/wet rubbing were evaluated, together with fabrics stiffness. types of textile fabrics using pigment dyes.The highest K/S is obtained and the fastness properties range between good and excellent for samples printed using methyl methaacrylate styrene (MMA) based, this is true irrespective of the type of printed fabric. The lowest K/S is obtained in case of using ethyl acrylate styrene (EA) as a commercial binder. The binder of 2-ethylhexylacrylate (2-EHA) gives K/S better than the binder of butyl acrylate styrene (BA) for two types of printed fabrics.